The INFLUENCE OF EXAMPLE AND HABITS METHODS ON ISLAMIC CHARACTER: A COMPARATIVE STUDY IN MIN 3 GARUT AND SDTQ AL IKHLAS - Jalal, M Rifky Faisal; Munawar Rahmat; Elan Sumarna (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Purpose: This study aims to examine the influence of the role model and habituation methods on the formation of Islamic character in students at two elementary educational institutions, namely MIN 3 Garut and SDTQ Al Ikhlas. Background: Against the background of the importance of Islamic character education as an antidote to moral challenges in the era of globalization, this study explores the effectiveness of both methods comparatively and simultaneously in forming character based on Islamic values. Method: A quantitative approach with multiple linear regression analysis method was used to examine the relationship between the role model and habituation variables with Islamic character. The study population included all sixth-grade students at both schools with a saturated sample of 29 people. Result: The results of the analysis indicate that both the role model and habituation methods have a positive and significant influence on the formation of Islamic character, with habituation showing a slightly more dominant contribution. The regression model also indicates that the combination of both methods is able to optimally improve the Islamic character of students. The differences in the application context of the two methods in each institution suggest that the integration of contextual and synergistic methods is more effective. This study confirms that teacher role models as role models and the habituation of Islamic values through routine activities play a strategic role in the formation of Islamic character. Conclusion: The practical implications emphasize the need to strengthen both approaches in the curriculum and school management. Further research examining external variables that influence the effectiveness of the method, as well as long-term studies to measure the sustainability of the character development, is recommended.